On the ratio of the main agricultural sectors in the urban economy of the Principality of Moldavia (the end of the 16th century – beginning of the 18th century) - Zabolotnaia, Lilia (Balcanica Posnaniensia. Acta et studia, 2023)
The article considers the ratio of the leading agricultural sectors in the economic structure of Moldavian cities in the period from the end of the 16th century to the beginning of the 18th century. The study attempts to systematise the available historical material (various sources of that era) based on the mathematical method and mathematical modelling tools. The results of the study confirm the well-established facts that agricultural and trade and handicraft activities were basic in the urban economic infrastructure and were closely interconnected. The dominance of the agrarian factor in urban life and the semi-agrarian nature of the towns of the Principality of Moldavia contributed to significant functional changes in the evolution of the economic infrastructure of towns and cities, the formation of the urban market, trade and market relations, craft formations, and so on for the following centuries.